Epigenetic Alterations in Keloid a Possible Method to Find Novel Agents for Keloid Treatment - Budiyanto, Arief Budiyanto; Wirohadidjojo, Yohanes Widodo (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Keloids are dermal fibro-proliferative disorders due to prolonged wound healing processes with excessive collagen depositions, which produce symptoms of itching and pain, cosmetic disfigurement, and limitation of joint motion. Standard treatment for keloid has not been accepted yet. It may be due to the complexities and poorly understood keloid development that are driven by various factors from systemic to local, genetic to epigenetic. Since genetic factors are difficult to manipulate, an approach to epigenetic factors may be hopeful. Purpose: To review various related reports on epigenetic factors such as DNA methylations, histone modifications, and micro-RNAs, which have significant roles in keloid development and can be used as targets for novel agents in keloid treatment. Review: Various genes in keloid fibroblasts (KFs) are repressed by DNA methylation, and one of them can inhibit the regulation of TGF-β1/Smad signaling, whereas another gene may influence anti-fibrotic events. Either inhibitor of methyl-transferase, inhibitor of histone-acetyltransferase, or histone-deacetylase can reduce TGF-β1/Smad signaling in KFs. Abnormal expressions of pro-fibrotic miRNAs have been identified in KFs and transfection KFs with anti-fibrotic miRNAs such as miRNA-205 and miRNA- 31, evidently can inhibit VEGF signaling. Furthermore, transfection of miRNA-637 into KFs can inhibit KFs in proliferation, migration, and collagen synthesis through TGF-β1/Smad signaling. Apoptosis and cellular senescence in KFs can also be stimulated by miRA-34 and miRNA-30. Conclusion: In the future, targets in epigenetic events such as inhibitors of methyl-transferase, histone-acetyltransferases, and histone-deacetylases, together with various miRNA, may be applied as novel agents for the treatment of keloid.